The high king's tomb - Britain, Kristen (DAW book collectors ;, 2007)
Karigan G'ladheon returns to the Green Riders, the magical messengers of the king, who desperately need her help in defeating an ancient evil, long dormant, that has just reawakened, determined to destroy the world.